A QUALITATIVE ANALYSIS OF SOCIAL HOUSING RESIDENTS - Beck, Andrew E. (My University, 2013)
The social determinants of health are the social and economic conditions in which people live that determine their health and housing is a determinant of health. The home holds important significance to individuals as it offers protection and privacy from the surrounding physical and social conditions, aids in the development of relationships, and is the centre of family life. However, many individuals are not able to experience the benefits stemming from an acceptable home.
This thesis explores the socio-economic aspects of housing through the transitional experiences of individuals moving from the private market level housing into rent-geared-to-income housing. The aim was to offer a descriptive account of individuals who have moved into social housing from private market housing and to find which of the dimensions of housing (physical conditions, psychological benefits, social environment and financial dimensions) most definitely contribute to individuals' everyday lives, health and well-being.
Through the use of in-depth interviews, this cross-sectional research study involves 12 individuals paying rent-geared-to-income and living in social housing in Hamilton, Burlington and Oakville, Canada.
Individuals reported several improvements to the different dimensions of housing that can influence health. Better housing conditions did improve their general and mental health. Individuals reported a greater sense of security, autonomy and self-identity. Social interactions and support were more commonly experienced and individuals did feel a decrease in the burden of rent. The most substantial changes were living in a less stressful environment and the financial security of social housing.
This thesis shows that securing social housing had an influence on participants' everyday lives, health and well-being. The findings may contribute to literature on the impacts of affordable housing on lower-income individuals’ health and well-being. Additionally, the findings have important housing policy implications for addressing affordable housing.
Keywords: rent-geared-to-income; health; public housing; seniors; subsidized housing; Human Geography; Human Geography